Increased diversification rates follow shifts to bisexuality in liverworts. Issue 3 (1st February 2016) - Laenen, Benjamin; Machac, Antonin; Gradstein, S. Robbert; Shaw, Blanka; Patiño, Jairo; Désamoré, Aurélie; Goffinet, Bernard; Cox, Cymon J.; Shaw, A. Jonathan; Vanderpoorten, Alain
Summary: Shifts in sexual systems are one of the key drivers of species diversification. In contrast to angiosperms, unisexuality prevails in bryophytes. Here, we test the hypotheses that bisexuality evolved from an ancestral unisexual condition and is a key innovation in liverworts. We investigate whether shifts in sexual systems influence diversification using hidden state speciation and extinction analysis (HiSSE). This new method compares the effects of the variable of interest to the best‐fitting latent variable, yielding robust and conservative tests. We find that the transitions in sexual systems are significantly biased toward unisexuality, even though bisexuality is coupled with increased diversification. Sexual systems are strongly conserved deep within the liverwort tree but become much more labile toward the present. Bisexuality appears to be a key innovation in liverworts. Its effects on diversification are presumably mediated by the interplay of high fertilization rates, massive spore production and long‐distance dispersal, which may separately or together have facilitated liverwort speciation, suppressed their extinction, or both. Importantly, shifts in liverwort sexual systems have the opposite effect when compared to angiosperms, leading to contrasting diversification patterns between the two groups. The high prevalence of unisexuality among liverworts suggests, however, a strong selection for sexual dimorphism.